1993
DOI: 10.1164/ajrccm/148.6_pt_1.1541
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Rifampin, Rifabutin, and Rifapentine for Preventive Therapy of Tuberculosis in Mice

Abstract: To identify alternative regimens for preventive therapy of tuberculosis, the pharmacokinetics and antimicrobial activities of rifampin (RMP), rifabutin (RBT), and rifapentine (RPT) were compared in BCG-vaccinated and M. tuberculosis-infected immunocompetent mice. RPT showed the highest serum peak level (Cmax) and the longest half-life (t1/2), whereas RBT displayed the lowest Cmax and the shortest t1/2. On weight-to-weight basis, both RPT and RBT were more bactericidal than RMP. The activity of RMP was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 23 publications
2
88
0
Order By: Relevance
“…In Group 6 mice that received twice-weekly P 15 HZ, and especially in Group 7 mice that received twice-weekly P 20 HZ, the cfu counts were lower than in control mice treated with daily RHZ. These results provide support for the dose-dependent activity of P, and are in agreement with what has previously been observed with R (22). Finally, the lung cfu counts were lowest in mice that received M 2 instead of H and twice-weekly P 15 (Group 8; 0.84 log 10 ) or P 20 (Group 9; 0.35 log 10 ) instead of R (p Ͻ 0.01 vs. daily RHZ).…”
Section: Treatment Efficacy In Studysupporting
confidence: 90%
See 1 more Smart Citation
“…In Group 6 mice that received twice-weekly P 15 HZ, and especially in Group 7 mice that received twice-weekly P 20 HZ, the cfu counts were lower than in control mice treated with daily RHZ. These results provide support for the dose-dependent activity of P, and are in agreement with what has previously been observed with R (22). Finally, the lung cfu counts were lowest in mice that received M 2 instead of H and twice-weekly P 15 (Group 8; 0.84 log 10 ) or P 20 (Group 9; 0.35 log 10 ) instead of R (p Ͻ 0.01 vs. daily RHZ).…”
Section: Treatment Efficacy In Studysupporting
confidence: 90%
“…In other words, the tubercle bacilli infecting mice treated with twice-weekly rifapentine were exposed to more free drug for longer periods of time than those in mice treated with daily rifampin, and this difference was reflected in the enhanced sterilizing activity of the twiceweekly rifapentine-containing regimens. It is tempting to speculate that the reduced rifampin exposure caused by autoinduction after the first few weeks of treatment significantly diminishes the activity of rifampin, as there is evidence in humans and in murine models that doses lower than 600 mg (10 mg/kg) are less effective (22,35,36). The greater drug exposures obtained with twice-weekly rifapentine-containing regimens may limit the reduction in activity that occurs with autoinduction.…”
Section: Discussionmentioning
confidence: 99%
“…Rifamycins have durable sterilizing activity against Mycobacterium tuberculosis, and the currently recommended 10 mg/kg dosage of rifampin, the most commonly used rifamycin, is at the low end of the dose-response curve (2)(3)(4)(5)(6)(7)(8)(9). Historically, selection of this rifampin dose seems to have been influenced by cost in the setting of incomplete dose-finding studies (10).…”
mentioning
confidence: 99%
“…Previously, it was shown that when INH was concomitantly given with RIF and PZA the AUC 0→∞ for RIF was significantly reduced by 39% when compared with treatment with RIF and PZA (25). As might be predicted by the substantial difference in the time to peak serum level (Tmax) between INH (0.24 h) and RPT (10.7 h), no difference was observed in the AUC 0→∞ when RPT was administered alone (179.5 g · h/ml) or in combination with INH-MXF (177.6 g · h/ml) (23,26).…”
Section: Discussionmentioning
confidence: 99%